Интенсификация и эффективность - Бачурин Александр Васильевич (Экономика, 1985)
Экземпляры: КХ (20120808) / Инвентарный номер: 852153 / Цена: 1.50 / Сис.шифр: 33С / Авт.знак: Б 32 / ГРНТИ: 06.91 / ББК: 65